(untitled) (Journal of Universal Science Research, 2023)
Diagnosis of diseases is one of the priorities in the development of modern medicine. Various data sources can be used for these purposes. Among such sources, medical images should be singled out, which reflect the microcosm of the phenomena under study. The study of medical images is possible based on the use of various image processing techniques. These techniques allow you to prepare the input image for research and perform the necessary analysis. One of the image processing techniques is contrasting the input image. This procedure makes it possible to improve the quality of perception of a medical image, to make a preliminary stage of its processing. On the example of images that contain foci of fatty liver lesions, the procedure for contrasting the input image is considered. Examples for real medical images are given, the possibility and expediency of using the contrasting procedure are discussed.